Fire Retardant And Fungi Protection Materials For Wood Constructions (Journal of Pharmaceutical Negative Results, 2023)
Wood is one of the oldest building materials, which is widely used today. Together with a large the number of positive properties of wood as a construction material, it also has negative properties. These properties is flammability and degradation. The difference in the fragments released between contaminated surfaces can be partially caused by the differences in the material moisture conditions. As was shown in the experiments comparing fungal growth on agar and ceiling tiles, the moisture from agar can penetrate the thick layer of fungal growth and thus can increase the adhesion forces and reduce the release of fungal propagules. It should also be noted that the adhesion forces are higher for fungal fragments than for fungal spores due to the smaller size of the fragments. According to existing regulatory documents wood intended for use in construction, must be subjected to fire retardant and to fungi protection processing.